2009
DOI: 10.1073/pnas.0904899106
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical mechanisms of phase contrast in gradient echo MRI

Abstract: Recently reported contrast in phase images of human and animal brains obtained with gradient-recalled echo MRI holds great promise for the in vivo study of biological tissue structure with substantially improved resolution. Herein we investigate the origins of this contrast and demonstrate that it depends on the tissue ''magnetic architecture'' at the subcellular and cellular levels. This architecture is mostly determined by the structural arrangements of proteins, lipids, non-heme tissue iron, deoxyhemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
439
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 265 publications
(455 citation statements)
references
References 33 publications
13
439
3
Order By: Relevance
“…Against this hypothesis is the observation that the offset is greater in magnitude in the corpus callosum (which is perpendicular to the main magnetic field) than in the anterior commissure (which is close to parallel to the magnetic field~10-20°). Such a modulation is inconsistent with a recently proposed local microstructure contribution (He and Yablonskiy, 2009) that would be characterized by a term proportional to cos 2 (θ)-1/3 if it was assumed that the underlying microstructure of the AC and the CC fiber bundles would be exactly the same. The second mechanism that could explain the variation of polarity of the white gray matter contrast in the absence of myelin would be a variation of the local bulk susceptibility of the surrounding gray matter or of the white matter itself.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Against this hypothesis is the observation that the offset is greater in magnitude in the corpus callosum (which is perpendicular to the main magnetic field) than in the anterior commissure (which is close to parallel to the magnetic field~10-20°). Such a modulation is inconsistent with a recently proposed local microstructure contribution (He and Yablonskiy, 2009) that would be characterized by a term proportional to cos 2 (θ)-1/3 if it was assumed that the underlying microstructure of the AC and the CC fiber bundles would be exactly the same. The second mechanism that could explain the variation of polarity of the white gray matter contrast in the absence of myelin would be a variation of the local bulk susceptibility of the surrounding gray matter or of the white matter itself.…”
Section: Discussioncontrasting
confidence: 59%
“…Phase imaging is known to depend not only on the shape of the different structures with different susceptibilities (Marques and Bowtell, 2005;Salomir et al, 2003;Schafer et al, 2009) but also on local microstructure (He and Yablonskiy, 2009), on local anisotropy of the magnetic susceptibility (Lee et al, 2010b;Liu, 2010) and even on nonsusceptibility mechanisms such as water exchange mechanisms (Luo et al, 2010;Shmueli et al, 2011;Zhong et al, 2011). In this study the phase shift observed locally between adjacent structures that remain geometrically unchanged during development was used to estimate myelination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations